Reversión sexual en la trucha arcoíris (Oncorhynchus mykiss) mediante la aplicación de la hormona masculinizante 17 α-metiltestosterona en alevines ginogenéticos (Innovation & Development in Engineering and Applied Science, 2022)
In rainbow trout production there is a notable sexual dimorphism in size, weight gain and meat quality, so it is necessary to obtain monosex cardumes, genotypically females, but capable of producing semen and behaving as functional males. There are several methods for sexual control, such as ultraviolet irradiation of sperm, thermal shock, and pressure, which produce gynogenetic fry, economically desirable within this salmonids species. The objective of this research was to evaluate the percentage of sexual reversion (masculinization) in rainbow trout by using different doses of hormone. The highest percentage of reversion of the experimental group was obtained by applying 3mg of 17 α-methyltestosterone per kg of feed, supplied for 60 days. After this feeding period they continued with their normal diet until the end of the experiment. The results reported that with this treatment 86% of the females in the experimental group became masculinized and 14% presented intersex. The physical characterization of the species in terms of weight and height during the growth and development period was also carried out and it was concluded that throughout their growth there was an interaction between growth days and hormone application.